Analisis Kohesi Gramatikal dan Kohesi Leksikal dalam Berita Online Banten News Edisi Maret 2022 dan Pemanfaatannya sebagai Bahan AJar di SMP - Novita, Dewi (Universitas Mathla'ul Anwar Banten, 2022)
This study aims to: (1) find the form of grammatical cohesive lingual units contained in the Banten News Online News text. (2) Finding the form of lingual unit that has Lexical Cohesion in the Banten News Online News text (2) Describing the relationship between the meanings of the Cohesive lingual unit form in the Banten News Online News text (3) Describing the use as teaching materials in Indonesian language learning in secondary schools Upper (junior high). This type of research is descriptive qualitative. The source of data in this study is news text from online media Banten news. The data analysis technique used the literature review method. The data collection technique uses the listen and note method because the data is in the form of written data. The step begins with listening to all data sources, then by recording the data. The validity used in this study is triangulation theory. Cohesion analysis was carried out on 31 online news texts on the Banten News website. The results of the study collected as many as 940 data on the form of grammatical cohesion and lexical cohesion. From this research it is concluded that grammatical cohesion and lexical cohesion have a very important role in the cohesive element of a discourse, one of which is news text. Keywords: News text, Grammatical Cohesion, Lexical Cohesion.